Assessment of Housing Conditions and Clean Water Sources as Determinants of Environmental Health in Rural Areas of Tenggarong Seberang District, Indonesia - Abdul Ridho Dhafa Risqillah; Tirsa Aulia Juniarti; Siti Fadilah Harun; Ashri Rahmaya Nur; Angela Lionthin Salsa; Putri Fitria Listi; Ayudhia Rachmawati (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Community health status is strongly influenced by environmental factors, particularly housing conditions and access to clean water. Poor environmental quality increases the risk of environmentally related diseases such as diarrhea, skin infections, and acute respiratory infections (ARI). Objective : This study aimed to assess the physical quality of houses and sources of clean water as a basis for improving environmental health in rural areas. Research Methods/ Implementation Methods : A quantitative descriptive design with univariate analysis was employed in Bukit Pariaman Village, Suka Sari Hamlet, Tenggarong Seberang District. Data were collected through field observation, structured interviews, and questionnaires involving 57 household heads. Results : Findings revealed that 84.2% of houses had adequate ventilation and 73.7% had permanent walls, whereas 26.3% lacked sufficient natural lighting. Approximately 96.5% of households accessed clean water through piped water systems; however, 33.3% stored water in uncovered containers and 12.3% had wells located less than 10 meters from septic tanks, posing contamination risks. In addition, 70.2% of households owned private latrines, while 29.8% used shared facilities. Conclusion/Lesson Learned : Most households met the criteria for healthy housing, yet improvements are needed in lighting, water source distance, and water storage practices to minimize the risk of environmentally related diseases.